2012
DOI: 10.1177/0192512112447117
|View full text |Cite
|
Sign up to set email alerts
|

Causes and contexts of tax morale: Rational considerations, community orientations, and communist rule

Abstract: In political theory, the subject of tax morale is closely linked to issues of citizenship and civic duties. Research on tax morale, however, is still rather underdeveloped in political science. In this article, we systematically compare a rational considerations approach with an approach focusing on the influence of community orientations on an individual's tax morale. We expect that contexts varying with the existence and duration of communist rule have caused systematic differences in terms of the motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 54 publications
(45 reference statements)
0
14
0
1
Order By: Relevance
“…Indeed, horizontal trust has a strong impact on the individuals' tax morale. When the members of a community have a high trust in other taxpayers, their tax morale is increased (Çevik, 2016;Kondelaji et al, 2016;Martins and Gomes, 2014;Torgler, , 2005bTorgler and Schaffner, 2007;Torgler et al, 2008;Trüdinger and Hildebrandt, 2013). In opposition, where the perceived level of tax evasion is high and the other taxpayers are perceived as free riders, citizens' tax morale is lower (Alm and Gomez, 2008;Çevik, 2016;Frey and Torgler, 2007;Molero and Pujol, 2012;Torgler and Schaffner, 2007).…”
Section: Informal Institutions and Tax Moralementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, horizontal trust has a strong impact on the individuals' tax morale. When the members of a community have a high trust in other taxpayers, their tax morale is increased (Çevik, 2016;Kondelaji et al, 2016;Martins and Gomes, 2014;Torgler, , 2005bTorgler and Schaffner, 2007;Torgler et al, 2008;Trüdinger and Hildebrandt, 2013). In opposition, where the perceived level of tax evasion is high and the other taxpayers are perceived as free riders, citizens' tax morale is lower (Alm and Gomez, 2008;Çevik, 2016;Frey and Torgler, 2007;Molero and Pujol, 2012;Torgler and Schaffner, 2007).…”
Section: Informal Institutions and Tax Moralementioning
confidence: 99%
“…,Trüdinger and Hildebrandt (2013),Vythelingum et al (2017) Sense of community (including peer effect) tax moraleAndriani (2016),Barone and Mocetti (2011), Braithwaite and Ahmed (2005), Cyan et al (2016), D'Attoma (2015), Filippin et al (2013), Lubian and Zarri (2011), Molero and Pujol (2012), Russo (2013), Trüdinger and Hildebrandt (2013) Political participation and the intensity of discussing political matters with friends and family have negative effects on tax morale Sá et al (2015), Torgler (2012),Torgler and Schaffner (2007),Torgler et al et al (2016),Martins and Gomes (2014),Torgler ( , 2005b,Torgler and Schaffner (2007),Torgler et al (2008),Trüdinger and Hildebrandt (2013) Perception of tax fraud/ evasion (size)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the state is expected to act in a trustworthy and fair manner in return, a logic that Frey and Torgler (2007) label "conditional cooperation". Indeed, previous studies have widely asserted that tax morale is highly correlated with trust in government (Andriani, 2016;Chan et al, 2018;Daude et al, 2012;Ibrahim et al, 2015;Kondelaji et al, 2016;Leonardo, 2011;Li, 2010;Ristovska et al, 2013;Torgler, 2012;Torgler & Schaffner, 2007;Torgler & Schneider, 2004;Trüdinger & Hildebrandt, 2013;Vythelingum et al, 2017). To evaluate this normative pillar, therefore, the following hypothesis is tested:…”
Section: Tax Morale and Neo-institutional Theory: Literature Review And Hypotheses Developmentmentioning
confidence: 99%
“…A shared concept of belonging to this polity motivates some individuals to pay taxes as a way of contributing to the wider community to which they belong. Previous studies, for example, have revealed that patriotism and nationalism (i.e., identification with the country) promote tax morale because they imply a greater attachment to the nation (Bilgin, 2014;Kondelaji et al, 2016;Leonardo & Martinez-Vazquez, 2016;MacGregor & Wilkinson, 2015;Martinez-Vazquez & Torgler, 2009;Martins & Gomes, 2014;Ristovska et al, 2013;Trüdinger & Hildebrandt, 2013). When citizens view themselves more as a citizen of a country, rather than a member of an ethnic community or a religious sect, then they will be more likely to pay their taxes to the government of that country to which they view themselves as belonging.…”
Section: Tax Morale and Neo-institutional Theory: Literature Review And Hypotheses Developmentmentioning
confidence: 99%